Learning Environment and Inclusion of learners in Secondary Education in Uganda: Analysis of the Moderating role of Self-Efficacy and Disability Status - Opio, George; Ofoyuru, Denis Thaddeus; Hoppers, Catherine A. Odora (East African Journal of Education Studies, 2023)
The inclusion of learners in secondary education has been fundamentally associated with the learning environment. However, little is known about the relationships between types of learning environments and inclusion when moderated by self-efficacy and mediated by disability status. This study measured whether different types of learning environments were associated with inclusion differently and if self-efficacy and disability status mediated the relationships between learning environment and inclusion. In a cross-sectional study, 309 learners with and without disabilities were assessed for inclusion in secondary education, Self-efficacy, Disability status and Learning environment. Regression Analyses were used to measure the association between different types of Learning environment and inclusion and the moderating role of learner’s self-efficacy and disability status in the relationship between learning environment and inclusion in secondary education. The findings yielded that physical and social learning environments are the types of learning environments that significantly and independently predicted inclusion in secondary education. The physical learning environment was significantly correlated with social efficacy (B=. 18, P<. 001) and all four facets of inclusion: access (B=. 19, P<. 001), Presence (B=. 12, P<. 001), Participation (B=. 14, P<. 001) and Achievement (B=. 10, P<. 001). While Social environment also had appositive and stronger effect on social efficacy (B=. 27, P = .001) and facets of inclusion; access (B=. 33, P<. 001), presence (B=. 22, P<. 001), Participation (B=. 26, P<. 001), and achievement (B=. 20, P<. 001). Disability status was found not to relate significantly to self-efficacy and inclusion, but self-efficacy was positively associated with inclusion. The direct relation between learning environment and inclusion remained significant (B=. 33, P<. 001). However, self-efficacy and disability status did not mediate the relationship between learning environment and inclusion. Types of learning environments should be considered when implementing inclusion in secondary education. Psycho-educational intervention should consider the development of social efficacy as a key determinant of the inclusion of all learners in secondary education.